2005
DOI: 10.1002/ajim.20219
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary functions of wheat flour mill workers and controls in Ibadan, Nigeria

Abstract: The study concluded that wheat flour-mill workers in Nigeria are at an increased risk of developing abnormalities of lung functions compared with control subjects, and the dominant pattern of respiratory disease among them is airway obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
(27 reference statements)
3
8
1
Order By: Relevance
“…Similar studies conducted in Nigeria [ 8 ] showed that flour millers recorded significantly lower mean lung functions compared with control subjects with an increased risk of developing abnormalities of lung functions and there is an association on the overall mean pulmonary function to the duration of exposure of the flour mill workers.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Similar studies conducted in Nigeria [ 8 ] showed that flour millers recorded significantly lower mean lung functions compared with control subjects with an increased risk of developing abnormalities of lung functions and there is an association on the overall mean pulmonary function to the duration of exposure of the flour mill workers.…”
Section: Discussionsupporting
confidence: 52%
“…Flour dust is a heterogeneous substance with respiratory sensitizing properties and long-term exposure to it may cause acute or chronic respiratory disease [ 8 ]. Several studies showed that prevalence of sensitization for wheat allergens and fungal a-amylase and OAD is high among workers exposed to flour dust [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the difference in lung function among the races is unclear. However, low socioecomic factors, low birth weight and occupational exposure are predisposing factors for low lung function in Africa [10,11] .…”
Section: Discussionmentioning
confidence: 99%
“…45 Similarly, in other studies, it was found that all respiratory and allergic symptoms had a higher prevalence among bakers in comparison to the control group. 46,47 From the factors studied to find out whether it is an independent factor affecting peak expiratory flow rate was aeration of the workplace as it is known that the level of exposure affects the PEFR which in turn will be reflected on the lung function and affecting the degree of airflow obstruction and reduction in the peak expiratory flow rate. Good aeration of the workplace affects the level of exposure and consequently lung function (48).…”
Section: Discussionmentioning
confidence: 99%